2021
DOI: 10.3390/ijerph18116125
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Caregiving on Fear of COVID-19 and Post-Traumatic Stress Symptoms

Abstract: Caregiving has been associated with increased levels of fear and post-traumatic stress symptoms (PTSS) during COVID-19 pandemic. However, there is a lack of studies that analyze when the relationship between fear and PTSS occur, using informal caregiving as a moderator variable. To explore this moderating role, we conducted a cross-sectional online study between November 2020 and January 2021. A total of 503 men and women from the Spanish general population completed the survey. Sociodemographic and Covid-19-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…The higher concern is difficult to explain since in Italy, as in different parts of the world, the spread of the COVID-19 and the related mortality have hit males more than females. However, published literature together with ours showed gender differences, since females were more concerned about COVID-19, experienced higher levels of fear of COVID-19, and were more likely to accept the vaccine against SARS-CoV-2 [ 24 , 26 , 27 , 28 , 29 , 30 , 31 ]. Moreover, the perceived severity of COVID-19 was a key factor in using all three main COVID-19 public health measures, since respondents who received the first dose and (or single dose) were less likely to report concern following the second dose compared to those who have always used the three measures and were also willing to use them after the booster dose.…”
Section: Discussionmentioning
confidence: 60%
“…The higher concern is difficult to explain since in Italy, as in different parts of the world, the spread of the COVID-19 and the related mortality have hit males more than females. However, published literature together with ours showed gender differences, since females were more concerned about COVID-19, experienced higher levels of fear of COVID-19, and were more likely to accept the vaccine against SARS-CoV-2 [ 24 , 26 , 27 , 28 , 29 , 30 , 31 ]. Moreover, the perceived severity of COVID-19 was a key factor in using all three main COVID-19 public health measures, since respondents who received the first dose and (or single dose) were less likely to report concern following the second dose compared to those who have always used the three measures and were also willing to use them after the booster dose.…”
Section: Discussionmentioning
confidence: 60%
“…Study findings indicated that carers’ psychological wellbeing deteriorated during the pandemic. Frequently cited psychological concerns included fear (Carballo et al., 2021; Cohen et al., 2020; D’herde et al., 2021; Fisher et al., 2021; Ng et al., 2020; Simblett et al., 2021; West et al., 2021), depression (Altieri & Santangelo, 2020; Giebel et al., 2021; Li et al., 2021; Pongan et al., 2021; Rainero et al., 2021), anxiety (Borelli et al., 2021; Carcavilla et al., 2021; Consonni et al., 2021; Giebel et al., 2021; Hwang et al., 2021; Li et al., 2021; Ng et al., 2020; Pongan et al., 2021; Rainero et al., 2021; Salari et al., 2020; West et al., 2021; Zucca et al., 2021), stress/distress (Alexopoulos et al., 2021; Carballo et al., 2021; Cohen et al., 2020; Dhavale et al., 2020; Fisher et al., 2021; Longacre et al., 2021; Rainero et al., 2021; Rusowicz et al., 2021; Tam et al., 2021; Zucca et al., 2021), sleep disturbances (Azevedo et al., 2021; Carcavilla et al., 2021; Li et al., 2021) and dietary issues (Borelli et al., 2021; Carcavilla et al., 2021; Li et al., 2021; Makaroun et al., 2021; West et al., 2021). Increased psychological burdens were often linked to a reduction in support (Budnick et al., 2021; Lee et al., 2021; Macchi et al., 2021; Tsapanou et al., 2021), or a deterioration in the care recipient's health (Borelli et al., 2021; Yasuma et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Study findings indicated that carers' psychological wellbeing deteriorated during the pandemic. Frequently cited psychological concerns included fear (Carballo et al, 2021;Cohen et al, 2020;D'herde et al, 2021;Fisher et al, 2021;Ng et al, 2020;Simblett et al, 2021;West et al, 2021) 40% of carers believed their own health was more endangered compared to the period before the pandemic. More specifically, carers reported worries about contracting the virus or being quarantined (Vaitheswaran et al, 2020;Yasuma et al, 2021), while increased sedentary behaviour and screen time was documented by Greaney et al (2021).…”
Section: Decline In Psychological Wellbeingmentioning
confidence: 99%
“…Fear experienced by carers was reported by carers of cancer patients in Singapore [ 40 ] with 72.8% of carers reporting being ‘very much’ or ‘extremely’ fearful of the virus. Similarly, a survey of the Spanish general population [ 41 ] found that carers reported higher levels of post-traumatic stress symptoms compared to non-carers with the same levels of COVID-19 related fear. Our review identified that carers were wary of re-integrating into society as lockdown measures eased [ 19 ], showing even as the risk of contracting the virus lessened, carers were still afraid.…”
Section: Discussionmentioning
confidence: 99%